Civil Law Liability of Debtors in Credit Agreements with Individual Guarantees - Karuna Dewi; I Gede Agus Kurniawan (Journal of Law, Politic and Humanities, 2024)
Credit agreements with personal guarantees often cause legal problems when the debtor defaults. Individual guarantees cannot be bound with a mortgage instrument or fiduciary guarantee, thus increasing the risk for banks. This research aims to understand and systematically examine the concept of regulating personal guarantees according to positive law in Indonesia and the legal consequences that arise if the debtor defaults in a credit agreement with personal guarantees. This research uses normative juridical method with concept approach. The data sources of this research are primary legal materials such as laws and jurisprudence, as well as secondary legal materials such as legal textbooks and journals. The results show that personal guarantees have an important function in advancing the economy through lending. However, this guarantee also poses a high risk for banks if not accompanied by careful analysis. Law No. 4 of 2023 on Financial Sector Development and Strengthening strengthens the role of the Financial Services Authority in supervising credit agreements with personal guarantees to maintain financial sector stability.